Flagship: News for the Pirate Education Nation - Office of Teacher Education (My University, 2013)
Newsletter for the Walter and Daisy Carson Latham Clinical Schools Network, produced by the Office of Teacher Education, College of Education, East Carolina University. Previous title: Clinical Schools Network News. Print holdings in North Carolina Collection, Joyner Library.
Keywords: Teacher education; Walter and Daisy Carson Latham Clinical Schools Network